TINJAUAN KOSMOLOGI DALAM LONTAR BHUWANA SANGKȘÉPA - I Gede Agus Suparta (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2019)
Bhuwana Sangkșépa is a traditional literary work found in Bali. This Bhuwana Sangkșépa generally explains that Shiva has the highest essence in the universe. This text is siwaistic and is grouped into tattva knowledge. This Bhuwana Sangkșépa text was chosen to be studied in this study because it is a text that describes the teachings of cosmology, namely the creation and fusion of the universe and humans. In this text it is explained that God as the prime causa is the main cause of the existence of the world and covers the universe. In this text it is also explained that the universe was created and will also be fused, cyclic. This process of creation and fusion is explained also in the evolution of the samkhya cosmology which in the evolution of the samkhya cosmology describes the development and shrinkage of the universe. In addition, in the text also explained that the universe is composed by its level. The structure of the universe includes the upper layer (sapta loka), the bottom layer (sapta patala), and the constituent of the universe, namely; sapta dwipa, sapta parwata, sapta ocean, and sapta tirtha. The contribution made by the concept of cosmology to the Balinese is knowledge of the cosmos. This knowledge can complement all ritual understandings and other religious activities